2018
DOI: 10.18632/oncotarget.25337
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells in clinical research and monitoring patients with colorectal cancer

Abstract: Colorectal cancer remains a frequent disease to which screening and target therapy exist, but despite this is still marked by a high mortality rate. Even though radical surgery may be performed in many cases, patients relapse with metastatic disease. Circulating tumor cells were incriminated for tumor recurrence, that's why vigorous research started on their field. Owning prognostic and predictive value, it was revealed their usefulness in disease monitoring. Moreover, they may serve as liquid biopsies for gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 88 publications
0
31
0
1
Order By: Relevance
“…Among the obstacles are the presence of ITH (Levitin et al, 2018;Lim et al, 2019), limited knowledge on CTCs mechanism of action in cancer progression (shedding from the primary/metastasis tumor, survival in bloodstream, avoidance of apoptosis, colonization potentials and settlement in distant organs), the rarity of CTCs (0 to 10 CTCs/ml whole blood in 30% to 50% mCRC patients) (Zieglschmid et al, 2005), various sizes of CTCs and the lack of clinical validation (Millner et al, 2013;Rejniak, 2016;Kowalik et al, 2017;Bankó et al, 2019). In addition, there are only a few studies relating to CTCs pharmacogenomics and underlying survival mechanisms (Wang et al, 2018) as well as the cell-cell interactions in CRC microenvironment (Krog and Henry, 2018), and majority of them are based on experimental and theoretical extrapolations (Burz et al, 2018). For instance, Yu et al (2014) suggested that pharmacogenomic profiling of invasive CTCs could predict chemotherapy response and resistance, whereas Steinert et al (2014) identified upregulation of CD47 in concordance with the mark down-regulation of calreticulin, which were believed to mediate immune escape and survival mechanisms of CTCs in CRC.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the obstacles are the presence of ITH (Levitin et al, 2018;Lim et al, 2019), limited knowledge on CTCs mechanism of action in cancer progression (shedding from the primary/metastasis tumor, survival in bloodstream, avoidance of apoptosis, colonization potentials and settlement in distant organs), the rarity of CTCs (0 to 10 CTCs/ml whole blood in 30% to 50% mCRC patients) (Zieglschmid et al, 2005), various sizes of CTCs and the lack of clinical validation (Millner et al, 2013;Rejniak, 2016;Kowalik et al, 2017;Bankó et al, 2019). In addition, there are only a few studies relating to CTCs pharmacogenomics and underlying survival mechanisms (Wang et al, 2018) as well as the cell-cell interactions in CRC microenvironment (Krog and Henry, 2018), and majority of them are based on experimental and theoretical extrapolations (Burz et al, 2018). For instance, Yu et al (2014) suggested that pharmacogenomic profiling of invasive CTCs could predict chemotherapy response and resistance, whereas Steinert et al (2014) identified upregulation of CD47 in concordance with the mark down-regulation of calreticulin, which were believed to mediate immune escape and survival mechanisms of CTCs in CRC.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Over the years, several mechanisms have been proposed to explain the metastatic progression in CRC, mainly via disturbance of cellular processes, epigenetic modifications, and genomic alterations (Herceg and Hainaut, 2007;Wong et al, 2007;Kanwal and Gupta, 2012;Arvelo, 2015). Aside from conventional treatment, in particular, chemotherapy (5-Fluorouracil, Oxaliplatin, Irinotecan and Capecitabine), many new targeted agents are also available for metastatic CRC (mCRC), including vascular endothelial growth factor (VEGF)-targeted therapy (Bevacizumab) and anti-epidermal growth factor receptor (EGFR)-targeted therapy (Cetuximab and Panitumumab) (Riihimäki et al, 2016;Burz et al, 2018). Nevertheless, metastasis remains a challenge in treating CRC, and among the main reasons are mostly attributable to intratumoral heterogeneity (ITH) and the presence of circulating tumor cells (CTCs) (Worthley and Leggett, 2010;Séronie-Vivien, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although the surgical stress response can promote metastases formation it is important to emphasize that metastases occurring during the first years after resection of the primary tumor, most often originate from CTC's having arrived at their target organs years before the clinical diagnosis. The micrometastases may stay dormant for years and not progress until the perturbations from surgery promote their growth …”
Section: The Surgical Stress Responsementioning
confidence: 99%
“…Circulating tumour cells (CTCs) have been considered as a minimally or non-invasive diagnostic and prognostic biomarker in patients with colorectal carcinoma (CRC) [ 1 , 2 ]. Previous studies have shown that CellSearch could isolate only epithelial CTCs [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%